Dejection and self-assessment of quality of life in patients with lung cancer subjected to palliative care - Nowicki, Andrzej; Farbicka, Paulina; Krajnik, Małgorzata (Contemporary Oncology/Współczesna Onkologia, 2015)
Aim of the study: To evaluate the intensity of dejection and self-assessment of quality of life in patients with lung cancer from the start of palliative care until death. Material and methods: The study included 63 patients with lung cancer from the start of care until death in palliative medicine centers in Bydgoszcz in 2012–2013. The visual-analogue scale constituting part of the ESAS scale was used to assess dejection, while question number 30 of the EORTC QLQ-C30 was used for self-assessment of quality of life. Results : “Moderate” and “very” intense dejection initially occurred in 19 (30%) and 24 (38%), and in the 2nd assessment in as many as 23 (36%) and 30 (48%) patients. Average quality of life deteriorated in this respect by 0.09 in the two-step scale (p = 0.005). Increase in the intensity of “moderate” dejection occurred between the 1st and 3rd assessment. Initially it occurred in 2 (9%) patients and in 14 (66%) during the 3rd assessment. In contrast, the levels of “very” severe dejection did not change significantly between the 1st and the 3rd assessment. The average quality of life deteriorated by 0.23 points (p = 0.004). A significant relationship was found only between analgesic treatment and quality of life (p < 0.0005). Other factors such as age, time from diagnosis to start of treatment, place of residence, sex, or financial condition did not affect the quality of life. Conclusions : Self-assessment of the quality of life worsens with time. The intensity of dejection does not change in the last 3 weeks of life. In multivariate analysis, among the selected variables such as age, sex, place of residence, time from diagnosis to start of palliative care, financial condition, and type of painkillers used, only the latter has an impact on self-assessed quality of life.